The Genetic Engineering of Food and the Failure of Science – Part 1: The Development of a Flawed Enterprise - Lotter, Don (The International Journal of Sociology of Agriculture and Food, 2009)
A major conflict has developed in science and society between promoters and opponents of transgenic foods. Food, feed, and fiber products derived from transgenic agricultural crops are presented here as a different case from bacterial, industrial, and pharmaceutical crop transgenics and should be parsed from the larger transgenics industry for comprehensive re-evaluation and market roll-back. Reviewed is the development of the crop transgenics industry; the early influence of the biotechnology industry over the US federal regulatory agencies in the context of the development of minimal regulation; the basic technology of plant transgenics; the main transgenic crops, traits, and producing countries; consumer resistance to transgenic foods; industry problems with shrinking investments; the worldwide promotion of transgenic crops; and ecological issues of transgenic crops. Flaws in the one gene–one protein model, the foundation of transgenics, are reviewed in the context of the recent and ongoing restructuring of the science of genetics. Research on the mutational consequences of plant transgenics and its phenotypic ramifications such as allergens and novel proteins is discussed. Major research findings and ‘red flag’ incidents in the history of transgenic foods and feeds are reviewed that reflect the flaws in the genetic foundations of transgenics.